Inflammatory manifestations in patients with Shwachman–Diamond syndrome: A novel phenotype. Issue 7 (15th April 2020) - Furutani, Elissa; Shah, Ankoor S.; Zhao, Yongdong; Andorsky, David; Dedeoglu, Fatma; Geddis, Amy; Zhou, Yu; Libermann, Towia A.; Myers, Kasiani C.; Shimamura, Akiko
Abstract: Shwachman–Diamond syndrome (SDS) is an autosomal recessive multisystem disorder characterized by exocrine pancreatic dysfunction, bone marrow failure, and leukemia predisposition. Approximately 90% of cases are due to biallelic mutations in the Shwachman–Bodian–Diamond ( SBDS ) gene. Additional phenotypic features variably associated with SDS include skeletal, neurologic, hepatic, cardiac, endocrine, and dental abnormalities. We report five subjects with SDS who developed a range of inflammatory manifestations. Three patients developed inflammatory eye conditions. Single cases of juvenile idiopathic arthritis, chronic recurrent multifocal osteomyelitis, and scleroderma were also noted. Clinical presentation and treatment responses are described. Proteomic analysis revealed increased inflammatory signatures in SDS subjects as compared to controls. Treatment of inflammatory manifestations in patients with SDS may be complicated by potential myelosuppressive toxicities of anti‐rheumatic medications. Further research is needed to better understand the potential link between inflammatory disorders and SDS to inform effective treatment strategies.